النقد الأدبي والهوية عمليات تأصيل النقد العربي الحديث - أبو هيف, عبد الله (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
واجه النقد العربي الحديث هيمنة المؤثرات الأجنبية إلى حدّ الاستلاب الكامل ، مما دفع الكثير من النقاد العرب إلى ابتعاث المكونات التقليدية الموروثة وتشكلاتها النقدية الحديثة ، وتجلت عمليات التصارع النقدي بين الهوية والهيمنة في إثراء التأصيل والتحديث النقدي ، لا مجرد استحضار الموروثات التقليدية ، أو مجرد نقل النظريات النقدية المترجمة وتطبيقاته. ثم آلت هذه التصارعات غالباً إلى ضبط مفهوم الأصالة والمعاصرة ومكانته في تحديد الهوية القومية ، وفي مقدمتها السمات النظرية النقدية تفاعلاً بين التراث النقدي وتثميره في المناهج النقدية الحديثة ، منظورات ومعايير . مهّد البحث عمليات تأصيل النقد العربي الحديث ، ولا سيما إبراز أهم النقاد الفاعلين في المنهجية والمعرفية والعلمية نشداناً للتعالق بين الموروثات والأشكال الحداثية وما وراءها . حلل البحث نماذج تمثيلية لشغل النقاد البارزيين دلالة على طبيعة التأصيل وشؤونه ومراميه ، عند النقاد محي الدين صبحي ( سورية ) ووجيه فانوس ( لبنان ) ، وعبد الفتاح بومدين ( السعودية ) ، وعبد الملك مرتاض (الجزائر ). استخلص البحث التوازي بين أصالة النقد العربي الحديث والاتجاهات الحداثية المتعددة ومنظوراته ومعاييره. Modern Arab Criticism has been confronted the domination of foreign effects to the extent of complete absorption; this has motivated many Arab critics to revive inherited traditional components and their modern critical formations. The critical conflict process between identity and domination has manifested itself in enriching the originality and modernization of criticism, not just by recalling traditions or by mere transforming translated critical theories and their applications. Then, these conflicts have mostly led to controlling the concept of originality and contemporariness and its role in specifying national identity starting with theoretical critical properties in the form of interaction between critical heritage and enriching it in modern critical approaches to perspectives and norms. This research introduces the process of originality of Modern Arab Criticism highlighting especially the most important and effective critics methodologically, intellectually, and academically, seeking the interaction between traditions and modernist forms. This study also analyzes representative models of the works of important critics illustrating the nature and purposes of originality, such as Mohie al-Din Sobhi (Syria), Wajih Fanous (Lebanon), Abd al-Fallah Bo madian (Saudi Arabia), and Abd al-Malek Murtad” (Algeria(. This research concludes with the parallelism between the originality of modern Arab criticism and the several modern trends of its perspectives and norms.